Renal Transplantation Dramatically Reduces IgA Anti-beta-2-glycoprotein I Antibodies in Patients with Endstage Renal Disease - Manuel Serrano; Jose Angel Martínez-Flores; Maria José Castro; Florencio García; David Lora; Dolores Pérez; Esther Gonzalez; Estela Paz-Artal; Jose M. Morales; Antonio Serrano (Journal of Immunology Research)
IgA anti-beta-2-glycoprotein I (aB2GPI) antibodies have been related to vascular pathology in the general population and mainly in hemodialyzed patients (prevalence 33%) in whom an elevated incidence of thrombosis and mortality is found. In this paper we have studied the presence of IgA aB2GPI antibodies at pretransplant and their evolution after transplantation with a cross-sectional-based follow-up study of a cohort of 288 endstage renal disease (ESRD) patients treated with kidney transplantation. Pretransplant IgA aB2GPI levels were elevated 31.7±4.2 U/mL without differences in age or type of dialysis. Patients with different etiologies of ESRD showed higher levels of IgA aB2GPI than blood donors, except the groups of non-IgA glomerular disease and systemic erythematosus lupus, whose nonsignificant differences were observed. IgA aB2GPI antibodies dropped immediately after transplantation (10.7±1.0 U/mL, P<0.0001), coinciding with a high degree of immunosuppression, and remained significantly lower than that observed in pretransplant status. Prevalence of patients with elevated antibodies was also less in transplanted patients (8.9% versus 30.4%, P<0.0001). Among, positivity for IgA aB2GPI was higher than in patients who had received their first transplant that those were retransplanted. This finding could have important clinical implications and can suggest new therapeutic strategies in patients with IgA aB2GPI antibodies.